Developing a best practice pathway to support improvements in Indigenous Australians' mental health and well-being: a qualitative study. Issue 8 (27th August 2015) - Hinton, Rachael; Kavanagh, David J; Barclay, Lesley; Chenhall, Richard; Nagel, Tricia
Abstract : Objective: There is a need to adapt pathways to care to promote access to mental health services for Indigenous people in Australia. This study explored Indigenous community and service provider perspectives of well-being and ways to promote access to care for Indigenous people at risk of depressive illness. Design: A participatory action research framework was used to inform the development of an agreed early intervention pathway; thematic analysis Setting: 2 remote communities in the Northern Territory. Participants: Using snowball and purposive sampling, 27 service providers and community members with knowledge of the local context and the diverse needs of those at risk of depression were interviewed. 30% of participants were Indigenous. The proposed pathway to care was adapted in response to participant feedback. Results: The study found that Indigenous mental health and well-being is perceived as multifaceted and strongly linked to cultural identity. It also confirms that there is broad support for promotion of a clear pathway to early intervention. Key identified components of this pathway were the health centre, visiting and community-based services, and local community resources including elders, cultural activities and families. Enablers to early intervention were reported. Significant barriers to the detection and treatment of those at risk of depression were identified, including insufficient resources, negative attitudes and stigma, and limited awareness of support options. Conclusions: Successful early intervention for well-being concerns requires improved understanding of Indigenous well-being perspectives and a systematic change in service delivery that promotes integration, flexibility and collaboration between services and the community, and recognises the importance of social determinants in health promotion and the healing process. Such changes require policy support, targeted training and education, and ongoing promotion.